Integrating refugees into labor markets - Pieter Bevelander (IZA World of Labor, 2020)
Refugee migration has increased considerably since the Second World War, and amounts to more than 50 million refugees. Only a minority of these refugees seek asylum, and even fewer resettle in developed countries. At the same time, politicians, the media, and the public are worried about a lack of economic integration. Refugees start at a lower employment and income level, but subsequently “catch up” to the level of family unification migrants. However, both refugees and family migrants do not “catch up” to the economic integration levels of labor migrants. A faster integration process would significantly benefit refugees and their new host countries.
Keywords: J15; J18; J21; J24; J61; 330; immigration; refugees; asylum; economic integration; resettlement